Developing a multisectoral National Action Plan for Health Security (NAPHS) to implement the International Health Regulations (IHR 2005) in Tanzania. Issue 2 (9th March 2018) - Mghamba, Janneth M; Talisuna, Ambrose O; Suryantoro, Ludy; Saguti, Grace Elizabeth; Muita, Martin; Bakari, Muhammad; Rusibamayila, Neema; Ally, Mohamed; Bernard, Jubilate; Banda, Richard; Mapunda, Maximillian; Eidex, Rachel; et al.
Abstract : The Ebola outbreak in West Africa precipitated a renewed momentum to ensure global health security through the expedited and full implementation of the International Health Regulations (IHR) (2005) in all WHO member states. The updated IHR (2005) Monitoring and Evaluation Framework was shared with Member States in 2015 with one mandatory component, that is, States Parties annual reporting to the World Health Assembly (WHA) on compliance and three voluntary components: Joint External Evaluation (JEE), After Action Reviews and Simulation Exercises. In February 2016, Tanzania, was the first country globally to volunteer to do a JEE and the first to use the recommendations for priority actions from the JEE to develop a National Action Plan for Health Security (NAPHS) by February 2017. The JEE demonstrated that within the majority of the 47 indicators within the 19 technical areas, Tanzania had either 'limited capacity' or 'developed capacity'. None had 'sustainable capacity'. With JEE recommendations for priority actions, recommendations from other relevant assessments and complementary objectives, Tanzania developed the NAPHS through a nationwide consultative and participatory process. The 5-year cost estimate came out to approximately US86.6 million (22 million for prevent, 50 million for detect, 4.8 million for respond and 9.2 million for other IHR hazards and points of entry). However, with the inclusion of vaccines for zoonotic diseases in animals increases the cost sevenfold. The importance of strong country ownership and committed leadership were identified as instrumental for the development of operationally focused NAPHS that are aligned with broader national plans across multiple sectors. Key lessons learnt by Tanzania can help guide and encourage other countries to translate their JEE priority actions into a realistic costed NAPHS for funding and implementation for IHR (2005).